Growth, climate change, and the critique of neoclassical reason: New possibilities for economic sociology - Matthew Soener (economic sociology_the european electronic newsletter, 2021)
The outlook on climate change is bleak. Warming effects from greenhouse gases mean rising sea levels, increased storms, droughts, wildfires, and other stresses to the Earth system. This means risks to our food supply, further species loss, and threats to coastal populations. Indirectly it means sociopolitical pressures in an already fragile context. Society's most vulnerable are already primary targets. And, if Covid-19 isn't grim enough, the combination of surface-level temperature increases combined with human- animal contact from deforestation and industrial farming will spawn more "zoonotic" infectious diseases. [...]
Keywords: 300